SMEs and Enterprises, Represent Potential Employment and Economic Growth in Emerging Economies in Albanian Development - MuÃ§ollari, Hava; Dumi, Alba; Kukaj, Lidra (Mediterranean Journal of Social Sciences, 2012)
Small and medium-sized enterprises (SMEs) are the backbone of all economies and are a key source of economicgrowth, dynamism and flexibility in advanced industrialized countries, as well as in emerging and developing economies.SMEsconstitute the dominant form of business organization, accounting for over 95% and up to 99% of enterprises depending on thecountry. They are responsible for between 60-70% net job creations in OECD countries. Small businesses are particularlyimportant for bringing innovative products or techniques to the market. Financing is necessary to help them set up and expandtheir operations, develop new products, and invest in new staff or production facilities. Many small businesses start out as anidea from one or two people, who invest their own money and probably turn to family and friends for financial help in return for ashare in the business. But if they are successful, there comes a time for all developing SMEs when they need new investment toexpand or innovate further. That is where they often run into problems, because they find it much harder than larger businessesto obtain financing from banks, capital markets or other suppliers of credit. This â€œfinancing gapâ€ is all the more important in a fastchangingknowledge-based economy because of the speed of innovation. Innovative SMEs with high growth potential, many ofthem in high-technology sectors, have played a pivotal role in raising productivity and maintaining competitiveness in recentyears. If SMEs cannot find the financing they need, brilliant ideas may fall by the wayside and this represents a loss in potentialgrowth for the economy.